Effectiveness of Tamarind (Tamarindus indica L.) Leaf Water Extract Against Root-Knot Disease (Meloidogyne spp.) on Tomato Plants - Sunarto, Toto; Irwan, Aep Wawan; Fatonah, Siti; Sudarjat, Sudarjat (CROPSAVER, 2025)
Root-knot disease is a major disease that attacks tomato plants. This disease is caused by the Root-knot nematode (Meloidogyne spp.), which can lead to significant losses in tomato crops. Farmers commonly use synthetic nematicides to control these nematodes, but excessive use of chemical agents can have negative effects. Tamarind leaf is a potential alternative that can be used as a botanical nematicide to control the nematodes that cause root-knot disease in tomato plants because it contains various secondary metabolite compounds, such as flavonoids. This research was conducted to determine the effectiveness of various concentrations of tamarind leaf aqueous extract in controlling Meloidogyne spp. nematodes. The experiment was carried out from May to July 2025 in the Plant Nematology Laboratory Division and Greenhouse of the Department of Plant Pests and Diseases, Faculty of Agriculture, Universitas Padjadjaran. The experiment used a Randomized Block Design (RBD) with seven treatments and four replications, consisting of a control, tamarind leaf aqueous extract at 2%, 4%, 6%, 8%, 10%, and carbofuran at 2g/tanamn. The results showed that the application of Tamarindus indica leaf water extract was effective in suppressing root-knot disease (Meloidogyne spp.) in tomato plants. T. indica leaf water extract at a concentration of 6% can suppress the number of galls on tomato plant roots by up to 64.91% and can suppress the number of second juvenile (J2) Meloidogyne spp. in 100 ml of soil by up to 71.18%.